Understanding pedestrian behavior and spatial relations: A pedestrianized area in Besiktas, Istanbul - Yildirim, Ozge Ceylin; Celik, Elif (KEAI PUBLISHING LTD, 2023)
This research provides a mixed method of investigating and analyzing pedestrian behavior in pedestrianized areas, which is one of the human-based urban development practices. The relationship between pedestrian behavior and perception of the city is discussed through a combination of architect and urban planner Gordon Cullen's theory and Space Syntax methodology. This study examines the development and implementation of the methodology to understand the relationship between pedestrian behavior and space in Besiktas Koyici settlement, Istanbul. The methodology, integrated with on-site observations (observing 10 min at five different observation points in the settlement at predetermined times on weekdays and weekends), surveys (determining pedestrian movement and perception in terms of Cullen's theory) and spatial configuration (Space Syntax analysis (connectivity, integrity) done with DepthMapX software), aims to analyze pedestrian behavior patterns. The concepts of sense of place and content, as well as the effects of their sub-concepts on their behaviors, were revealed because of a survey conducted with students and architects of variety of educational levels who are daily users of the field. Pedestrian counting and observations were used to create density, activity, and mobility maps of the area. It has been found that pedestrianized areas have a significant impact on pedestrian behavior through influencing vitality and appeal and that Cullen's theory may be used to analyze pedestrian behavior and perceptions of the city. The study showed that spatial configuration and Cullen's theory effect pedestrian movement by complementing each other.(c) 2022 Higher Education Press Limited Company. Publishing services by Elsevier B.V. on behalf of KeAi Communications Co. Ltd. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Pedestrian behavior; Pedestrianization; Besiktas; Gordon Cullen?s theory; Space syntax; WALKING; NETWORK; ATTRIBUTES; VISIBILITY; MOVEMENT; LOCATION; ISOVISTS; PATHWAY; DESIGN; Architecture